Thermodynamic and kinetic parameters of biomass from black pine (PINUS NIGRA ARN.) - Tasheva Stanislava (EDP Sciences, 2021)
The aim of the present study was to determine the thermodynamic and kinetic parameters of biomass obtained from black pine (Pinus nigra Arn.). The biomass, consisting of twigs with needles and needles alone of black pine, was used. Ultimate analysis with the elemental composition of the biomass with respect to the main components such as carbon (C), hydrogen (H), nitrogen (N), and sulfur (S) of the biomass before and after water distillation was made. The high heating value (HHV) and low heating value (LHV), energy density and fuel value index were determined. Thermodynamic (Gibbs energy, enthalpy, and entropy) and kinetic (activation energy, the rate constant of the process, and reaction order) parameters of the biomass were calculated.